Developing a Canadian Real-World Evidence Action Plan across the Drug Life Cycle - Tadrous, Mina (Healthc Policy, 2020)
Policy makers face challenges with the number of drugs for rare indications and rapidly rising costs. In facing these challenges, decision-makers see real-world evidence (RWE) as an opportunity. Health Canada and the Canadian Agency for Drugs and Technologies in Health (CADTH) recently announced their intent to co-develop an action plan to optimize the process for the systematic use and integration of RWE into both regulatory and reimbursement decision-making in Canada. When implemented, this will have a significant impact on how drugs are approved and paid for in Canada. We highlight the key opportunities, barriers and future directions related to the use of RWE throughout the life cycle of drugs in Canada.